2020
DOI: 10.1021/acs.jpclett.0c02831
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Origin of Electrical Conductivity in Gold–Polythiophene Hybrid Particle Films

Abstract: Hybrid electronic materials combine inorganic metals and semiconductors with π-conjugated polymers. The orientation of the polymer molecules in relation to the inorganic components is crucial for electrical material properties and device performance, but little is known of the configuration of π-conjugated polymers that bind to inorganic surfaces. Highly curved surfaces are common when using nanoscale components, for example, metal nanocrystal cores covered with conductive polymers. It is important to understa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 71 publications
0
6
0
Order By: Relevance
“…Our experimental conditions lead to isometric NPs, and we suggest that the main role of CTAB in our synthesis is to prevent particle aggregation. Silver in different states has been found on surface gold particles, , both as CTAB–silver bromide complex and as adsorbed AgBr 2– species . Monolayers or submonolayers of Ag(0) on gold nanoparticles have also been reported .…”
Section: Results and Discussionmentioning
confidence: 99%
“…Our experimental conditions lead to isometric NPs, and we suggest that the main role of CTAB in our synthesis is to prevent particle aggregation. Silver in different states has been found on surface gold particles, , both as CTAB–silver bromide complex and as adsorbed AgBr 2– species . Monolayers or submonolayers of Ag(0) on gold nanoparticles have also been reported .…”
Section: Results and Discussionmentioning
confidence: 99%
“…46,47 Their molecular configuration depends on the crystallographic orientation and the curvature of the Au surface. 48…”
Section: Resultsmentioning
confidence: 99%
“…46,47 Their molecular conguration depends on the crystallographic orientation and the curvature of the Au surface. 48 We used the commercial PEDOT:PSS aqueous dispersion Clevios™ P that contains swollen, gel-like PEDOT:PSS particles of diameter d 50 ¼ 80 nm at a PEDOT : PSS weight ratio of 1 : 2.5 and a pH of 1.9 without any additives. 49,50 While its acidity is harmful for AgNWs, 24 it does not etch AuNWs.…”
Section: Paper Nanoscale Advancesmentioning
confidence: 99%
“…However, to monitor the local temperature change, it is necessary to use sophisticated methods such as, for instance, fluorescent thermometry combined with DNA technology. 38 Note that in our hybrid system, emission from the polymer shell makes possible measurements of the lifetime of excited states (Figure 2d) which in principle is sensitive to the local temperature. Therefore, we postulate that the present system makes it possible to monitor the change of temperature in situ during a photocatalytic process.…”
mentioning
confidence: 98%
“…X-ray photoemission spectroscopy (XPS) further confirmed that the metal–polymer interface is maintained through the Au–S–C (S 2p, 160 eV) from thiophene moiety and Au–O bonds (O 1s, 529 eV) from sulfonate terminal groups (Figure b,d). The formation of π–π interactions between the thiophene rings (C 1s, 290.5 eV in Figure c) suggests that the polymer can form organized structures in either face-on or edge-on fashion. , It is reasonable to assume, however, that in the liquid phase, the hydrated polymer extends toward the bulk solution, resulting in a less compact structure. The hydrodynamic diameter of spherical nanoparticles increased by ∼10 nm after displacing native ligands with PTEBS as confirmed by dynamic light scattering analysis (Figure S2).…”
mentioning
confidence: 99%